Democracy, development, rule of law and criminal organizations in Latin America: The cases of Mexico and Colombia through the experiences of cartels (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The birth and development of modern criminal organizations is often the reflex of social, political, and economic dynamics of the territories where these organizations operate. The recent history of Latin America and of criminal organizations in Mexico and Colombia are clear representation of it. Only a transparent and democratic administration of justice can consolidate progresses made in the construction of modern rule of law democracies.
Keywords: criminal organizations, development, America Latina, Mexico, Colombia